The Implementation of Multicultural Education in Senior High Schools in Medan - Anwar Soleh Purba; Elly Malihah; Achmad Hufad (Budapest International Research and Critics University, 2019)
Multicultural education is one of learning that provides understanding and tolerance attitudes towardsdiversity. This study has reviewed the multicultural education system which will be the basis for children about the importance of diversity, whether the diversity in races, ethnicity, culture, religion, gender, economic status, and so forth. As for the research method used in this research is a constructive paradigm with a case study approach through observation, interviews, and documentation in the Yayasan Perguruan Sultan Iskandar Muda (YPSIM) to collect the data. To strengthen the data, the researchers prioritized informants who has a role in management structures, teachers, students from various ethnicities and religions as well as communities around the Yayasam Perguruan Sultan Iskandar Muda, Medan. The results of the study indicates that the Yayasan Perguruan Sultan Iskandar Muda Foundation has implemented a multicultural education program that has made students become more understand about the meaning of diversity and more tolerant of diversity in religion and ethnicity in Medan.